Fractional Laplace transforms—a perspective - Treumann, Rudolf A.; Baumjohann, Wolfgang (Frontiers in Physics, 2014)
A new form of the Laplace transform is reviewed as a paradigm for an entire class of fractional functional transforms. Various of its properties are discussed. Such transformations should be useful in application to differential/integral equations or problems in non-extensive statistical mechanics.